Unraveling households' natural resource management strategies: a case study in Jalisco, Mexico. Issue 1 (1st January 2020) - Monroy-Sais, Sofía; García-Frapolli, Eduardo; Mora, Francisco; Skutsch, Margaret; Casas, Alejandro; Gerritsen, Peter R. W.; Cohen-Salgado, Daniel; Ugartechea-Salmerón, Oscar
ABSTRACT: The analysis of resource management strategies is considered to be relevant to the conservation and sustainable use of ecosystems. In Mexico, ejidos are the most important of the land tenure institutions that grant access to resources inside communities. Although it is recognized that an ejido's internal structure creates different social groups, few studies have explored their resource management strategies. The aim of this study was to characterize natural resource management strategies in two ejidos in a highly biodiverse region on the southern coast of Jalisco, Mexico. We sought to identify differences in strategies and the variables that explain these differences. We took the household as the unit of analysis, and conducted 55 structured interviews that tackled different aspects of households' productive activities and natural resource management. We used cluster and ordination analyses to generate a typology of natural resources management strategies, and linear models to identify the variables that differed among groups. The results show that four different natural resources management strategies were strongly associated with differences in land tenure and the type of ecosystem that a household manages. This information can help us to enhance and diversify strategies for sustaining both ecosystems and community livelihoods.